2022
DOI: 10.21248/l1esll.2022.22.1.405
|View full text |Cite
|
Sign up to set email alerts
|

Swedish (L1) and English (L2) Argumentative Writing of Upper Secondary Students with Reading Difficulties

Abstract: Writing has been identified as a challenge for students with reading difficulties. This study contributes to previous research by exploring argumentative writing in L1 (Swedish) and L2 (English) in a group of students with reading difficulties in upper secondary school. Participants were 19 students with typical reading, 19 students with poor decoding, and 9 students with poor comprehension. A majority of students attended vocational programmes. Written text quality was assessed by using an adapted version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 33 publications
(77 reference statements)
1
10
0
Order By: Relevance
“…Content and conceptual development may be affected too. As to spelling, this group's performance has almost been on a par with control groups (Cragg and Nation, 2006;Re and Carretti, 2016), but research has also found opposite results (Sehlström et al, 2022).…”
Section: Reading Difficulties and Written Text Qualitymentioning
confidence: 84%
See 3 more Smart Citations
“…Content and conceptual development may be affected too. As to spelling, this group's performance has almost been on a par with control groups (Cragg and Nation, 2006;Re and Carretti, 2016), but research has also found opposite results (Sehlström et al, 2022).…”
Section: Reading Difficulties and Written Text Qualitymentioning
confidence: 84%
“…Researchers agree that poor reading comprehension may have a negative impact on written text quality ( Herbert et al, 2020 ; Kim, 2020 ). More specifically, students with poor reading comprehension have difficulties primarily at discourse-level, in such areas as text organization, for example, coherence, cohesion, cohesive devices ( Cox et al, 1990 ; Cragg and Nation, 2006 ; Carretti et al, 2013 , 2016 ; Re and Carretti, 2016 ; Sehlström et al, 2022 ), and lexical and grammatical complexity and syntactic diversity ( Carretti et al, 2013 , 2016 ; Re and Carretti, 2016 ). Content and conceptual development may be affected too.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Written text quality was examined using Jacobs et al's (1981) analytic scoring scheme. A slight adaptation was utilized as we subdivided the mechanics category into spelling and punctuation, which resulted in a total of seven aspects of text quality: content, organization, cohesion, vocabulary, language use, spelling, and punctuation (see Sehlström et al, 2022 for a detailed description). In this study, only spelling was used.…”
Section: Methodsmentioning
confidence: 99%